Library 2.0 : a guide to participatory library service - Casey, Michael E., 1967- (Information Today, 2007)
"Two of the first and most original thinkers on Library 2.0 introduce the essential concepts and offer ways to improve service to better meet the changing needs of 21st century library users. Describing a service model of constant and purposeful change, evaluation and updating of library services, and user participation, the book both outlines the theoretical underpinnings of Library 2.0 and provides practical advice on how to get there. From incorporating technology to reaching the long tail, from getting buy-in to maintaining momentum, all aspects of Library 2.0 are covered."--Page 4 of cover.